2009
DOI: 10.1002/pmic.200900326
|View full text |Cite
|
Sign up to set email alerts
|

When less can yield more – Computational preprocessing of MS/MS spectra for peptide identification

Abstract: The effectiveness of database search algorithms, such as Mascot, Sequest and ProteinPilot is limited by the quality of the input spectra: spurious peaks in MS/MS spectra can jeopardize the correct identification of peptides or reduce their score significantly. Consequently, an efficient preprocessing of MS/MS spectra can increase the sensitivity of peptide identification at reduced file sizes and run time without compromising its specificity. We investigate the performance of 25 MS/MS preprocessing methods on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 25 publications
1
59
0
Order By: Relevance
“…For each MS/MS spectrum, the 200 most intense fragment ions were converted into an .mgf file without any further data processing such as smoothing, deisotoping, and filtering. Comparisons between the .mgf files generated by our approach and those generated by DTASuperCharge showed that our approach performed favorably (26).…”
Section: Methodsmentioning
confidence: 98%
“…For each MS/MS spectrum, the 200 most intense fragment ions were converted into an .mgf file without any further data processing such as smoothing, deisotoping, and filtering. Comparisons between the .mgf files generated by our approach and those generated by DTASuperCharge showed that our approach performed favorably (26).…”
Section: Methodsmentioning
confidence: 98%
“…The ion trap was operated in datadependent acquisition mode, fragmenting up to six of the most intensive ions after each survey scan. The Thermo ".raw" files were converted into the Mascot generic format (mgf) by extracting the 200 most intense fragment ions for each MS/MS spectrum (14).…”
Section: Proteomic Analysis For Discovery Stage 1-gelc-ms/ms Methodmentioning
confidence: 99%
“…Database Searching-Peak lists of the 200 most abundant fragment ions from each product ion spectrum were extracted out of Thermo .raw files and converted into .mgf files using in-house software (21). No further data processing such as smoothing, de-isotoping, and/or filtering were carried out.…”
Section: Methodsmentioning
confidence: 99%